(untitled) (Global Journal of Science Frontier Research, 2012)
This study examined the congruency between extension professionals and farmers regarding their perceptions of privatization and commercialization of agricultural extension services. The study was carried out in Delta State, Nigeria and it had a sample size of 224 respondents comprising of 134 extension professionals of the Delta State Agricultural Programme (DTADP) and 90 farmers that were randomly selected. Data for the study were collected from the respondents through the use of validated questionnaire and interview schedule. The questionnaire was used for the extension professionals, while the interview schedule was used for the farmers. Spearman’s rank order correlation coefficient was used to determine the congruency in perceptions of respondents. Results of the study showed a high congruency between extension professionals’ perception and their estimate of farmers’ perception (rho = 0.92), while the congruency between farmers’ perception and their estimate of extension professionals’ perception was low (rho = 0.08). The study recommends that farmers’ knowledge of issues relating to P and C should be enhanced through seminars and workshops organized by the appropriate extension agency.